TOZ METALURJİSİ (TM) İLE ÜRETİLMİŞ Nİ-Tİ ALAŞIMLARININ DİFÜZYON KAYNAK YÖNTEMİYLE BİRLEŞTİRİLEBİLİRLİĞİNİN ARAŞTIRILMASI - DİKBAŞ, HALİL (Fırat Üniveristesi, 2005)
Bu çalışmada soğuk preslemeyle imal edilmiş Ni-Ti kompozitler difüzyon kaynağı ilebirleştirildi. Metal matrisli kompozit (MMK) malzeme, 45 Âµm boyutlarında ağırlıkça % 51 Nive % 49 Ti tozu karışımından üretilmiştir. Araştırmada hazırlanan kompozit malzemeler aynıbasınçta, farklı sıcaklık ve sürelerde difüzyon kaynağı ile birleştirilmiştir. Çalışmada özellikle,kaynak bölgesindeki Ni-Ti oranı incelenmiştir.Üretilen numuneler difüzyon fırını için uygun boyutlara getirilip, difüzyon kaynakyöntemi ile birleştirilmiştir. Difüzyon kaynakları argon koruyucu gaz atmosferinde, 500 N'lukdinamik yükleme ile, 20, 40 ve 60dk'lık sürelerde ve 850, 875, 900 ve 925 ºC sıcaklıklardayapıldı. Kaynak işlemlerinden sonra, numuneler kaynak birleşme ara yüzeyine dik olarakkesilip, birleşme ara yüzeylerinde mikro yapı, SEM, EDS analizi çalışmaları yapılmıştır.Yapılan optik mikroskop çalışmalarında, kompozitin homojen bir karışıma sahip olduğuve gözenek miktarının düşük olduğu görülmüştür. Ni-Ti oranlarının malzemenin farklınoktalarında yakın değerler taşıdığı görülmüştür.Anahtar Kelimeler: Soğuk presleme, Ni-Ti, MMK, difüzyon kaynağı, toz metalurjisi.

In this study, the by cold pressing manufactured Ni-Ti composites were joined withdiffusion bonding techniques. Metal tatrix composite (MMC) material has been produced asmixture with a average dimension of 45Âµm and with a chemical composition of 51 % Ni-49 %Ti in weight percent. In this study two parts with same chemical composition MMC were joinedby use diffusion welding technique. The bonding of MMC parts were relaized under the samepressure, at different temperatures and durations. Particularly, the Ni-Ti rate in the weldingregion was examined.The manifactured samples were cut in a suitable dimensions and they have been joinedin a diffusion furnace with diffusion welding method. Diffusion welding process were madeunder argon inert gas atmosphere, with a constant load of 500 N, under the temperature of 850,875, 900 and 925ºC and, in 20, 40 and 60 minutes experiment time. After the weldingprocesses, samples were cut perpendicular to the welded surface, the microstructure wereexamined by SEM and EDS analysis on the near of bonded surface layer, and also matrix.the optical microscopy photos have been shown that the bonded composite materials hadahomogen structure and a minimumhole level. It was also observed that the Ni-Ti rates hadapproximately, the same values in different point of the test materials.Keywords: Cold pressing, Ni-Ti, MMC, diffusion bonding, powder metallurgy,
The investigation of bondability of Ni-Ti alloys by powder metallurgy method with the diffusion bonding
Keywords: Metalurji Mühendisliği